How Do Consumers Use Nutrition Labels on Food Products in the United States?. Issue 2 (April 2017) - Zhang, Yuanting; Chen, John T.; Wang, Suohong; Andrews, J. Craig; Levy, Alan
Abstract : This study examined how consumers use food labels in the United States. Based on the results from the cluster analysis, eight nutrition label questions from the Health and Diet Survey fell into 2 categories of label usage: for shopping or for dietary decisions. Survey respondents reported equal or more consideration of nutrition-label information for dietary choices than for shopping decisions in 2008 compared with prior survey years. Female consumers, frequent label users, well-educated, consumers aged 50 to 59, or consumers with any health issues were significantly more likely to use food labels for all kinds of purposes than their corresponding counterparts.